PENINGKATAN HASIL BELAJAR LARI ESTAFET MELALUI PENDEKATAN SAINTIFIK PADA SISWA KELAS VI SD NEGERI SALAMAN 4 TAHUN 2016 - Marwoto, Widodo Giri (Journal of Physical Education Health and Sport, 2016)
The purpose of this study is to improve learning outcomes relay through a scientific approach in Class VI SDN Salaman Salaman 4 districts of Magelang regency in 2016. This study is a Class Action Research. Subjects were students in sixth grade elementary school districts Salaman Salaman IV Magelang regency amounting to 24 students. Data collection methods used were observation and tests of performance, processing data using descriptive percentage. Based on the research results in cycle 1, the cognitive aspect completed 66.6%, 34.4% did not complete, thorough afekif aspects of 20.83% and 79.16% did not complete due psychomotor aspects of incomplete 58.3% and 41.7% , student learning outcomes in classical complete 14 students (58.3%) and 41.7% did not complete the study on results in cycle 2, the cognitive aspect completely 100%, 91.66% completed afekif aspect is not finished 8.33%, psychomotor aspects completed 79.16% 20.83% is not exhaustive and completeness of student learning outcomes in the classical 21 students (87.5%), 12.5% did not complete. In this study showed that an increase in the classical mastery learning outcomes by 29.5%, from cycle 1, 58% increased to 87.5% in cycle 2. Thus we can conclude that the scientific approach can improve learning outcomes relay in class VI SDN Salaman Salaman 4 subdistrict of Magelang regency in the academic year 2015/2016.